PENGARUH METODE MEANINGFUL INSTRUCTIONAL DESIGN (MID) TERHADAP KEMAMPUAN KOGNITIF SISWA PADA MATA PELAJARAN QUR’AN HADITS KELAS X DI MAN 1 KUDUS - Achmad Abdul Azis (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2021)
The Meaningful Instructional Design (MID) method is a method that prioritizes learning meaningfulness and effectiveness by creating a cognitive-constructivism framework-activity conceptual framework. Students' cognitive ability is one of the domains in the taxonomy of education, Cognitive theory emphasizes how the process or efforts to optimize the ability of rational aspects or thinking abilities possessed by others. The problems of this research are as follows: 1) To what extent is the implementation of the Meaningful Instructional Design (MID) method on the subject of Qur'an Hadith class X at MAN 1 Kudus?. 2) To what extent are the students' cognitive abilities in the subject of Qur'an Hadith class X at MAN 1 Kudus?. 3) Is there any effect of the Meaningful Instructional Design (MID) method on the cognitive abilities of students in the class X Qur'an Hadith subject at MAN 1 Kudus?. This study uses a quantitative approach with data collection techniques used through questionnaires, observations, interviews and documentation of related agencies at MAN 1 Kudus. The results of this study are as follows: 1) The implementation of the Meaningful Instructional Design (MID) method on the subjects of the X Qur'an Hadith class at MAN 1 Kudus is considered to have a good influence because the results of the mean (average) questionnaire method of Meaningful Instructional Design (MID) shows a value of 80.48 from 40 respondents and is included in the interval (78-81) which is the